Book Review: Sandeep Bakshi, Suhraiya Jivraj and Silvia Posocco (eds), Decolonizing Sexualities: Transnational Perspectives, Critical Interventions - Narrain, Siddharth (feminists@law, 2018)
Book review of Sandeep Bakshi, Suhraiya Jivraj and Silvia Posocco (eds), Decolonizing Sexualities: Transnational Perspectives, Critical Interventions (Counterpress, Oxford, 2016).